2017
DOI: 10.1080/10245332.2017.1418610
|View full text |Cite
|
Sign up to set email alerts
|

Balancing relapses versus cognitive impairment in primary central nervous system lymphoma: a single-center experience

Abstract: The low-dose WBRT consolidation is associated with lower PCNSL relapses with only mild neurocognitive toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Although most patients experience remission after initial treatment, increased relapse can be observed with prolonged follow-up, and consolidation therapy maintains the state after induction therapy; thus, initial consolidation therapy may play an important role in relapsed PCNSL ( 39 , 40 ). Chanswangphuwana et al.…”
Section: Relapse Rate and Relapse-related Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most patients experience remission after initial treatment, increased relapse can be observed with prolonged follow-up, and consolidation therapy maintains the state after induction therapy; thus, initial consolidation therapy may play an important role in relapsed PCNSL ( 39 , 40 ). Chanswangphuwana et al.…”
Section: Relapse Rate and Relapse-related Factorsmentioning
confidence: 99%
“…Chanswangphuwana et al. ( 40 ) retrospectively analyzed the effect of whole-brain radiation therapy (WBRT) as a consolidation therapy in patients with PCNSL relapse, and some of the 37 patients with newly diagnosed PCNSL underwent WBRT after initial remission. The results showed that among the 22 patients with CR, PFS was significantly lower in patients without WBRT than in patients with WBRT, and the 3-year PFS rates were 35% and 78.75%, respectively.…”
Section: Relapse Rate and Relapse-related Factorsmentioning
confidence: 99%
“…Of the 42 included studies on cognitive functioning, 24 measured objective cognitive performance, including digital span, trail-making test, conversion speeds, and complex figure test (Abrey et al, 2003; Correa et al, 2019; Correa et al, 2004; Correa et al, 2009; Correa et al, 2012; Dahlborg et al, 1996; Doolittle, Dósa, et al, 2013; Ferreri et al, 2017; Fliessbach et al, 2005; Fliessbach et al, 2003; Juergens et al, 2010; McAllister et al, 2000; Morris et al, 2013; Neuwelt et al, 1991; Neuwelt et al, 2005; Nilles et al, 2022; Omuro, Chinot, et al, 2015; Omuro, Correa, et al, 2015; Pels et al, 2003; Pertz et al, 2021; Schlegel et al, 2001; Shah et al, 2007; van der Meulen et al, 2021; Wiemann et al, 2020). 14 studies examined only subjective cognitive functioning (Batchelor et al, 2003; Chanswangphuwana et al, 2018; Fisher et al, 2005; Gao et al, 2016; Glass et al, 2016; Herrlinger et al, 2017; Illerhaus et al, 2016; Illerhaus et al, 2008; Kaburaki et al, 2017; Kiefer et al, 2012; Laack, Ballman, Brown, & O'Neill, 2006; Laack et al, 2011; O’Neill et al, 1999; Shan et al, 2014). The effect of treatment on both outcomes was described in 4 articles (Ferreri et al, 2022; Houillier et al, 2019; Ichikawa et al, 2014; Nilles et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The two-year survival was about 60–70%, and the five-year survival could be increased to 22–40%. Chanswangphuwana et al [ 31 ] retrospectively analyzed the effect of WBRT as consolidation therapy in patients with PCNSL relapse, and some of the 37 patients with newly diagnosed PCNSL underwent WBRT after initial remission. The results showed that among the 22 patients with CR, progression-free survival (PFS) was significantly lower in patients without WBRT than in patients with WBRT, and the 3-year PFS rates were 35% and 78.75%, respectively.…”
Section: Discussionmentioning
confidence: 99%